2022
DOI: 10.1016/j.rmra.2021.11.183
|View full text |Cite
|
Sign up to set email alerts
|

Profil anamnestique, clinique, biologique, radiologique et évolutif de la COVID-19 en fonction des maladies cardiovasculaires : étude comparative

Abstract: Introduction L’infection SARS-CoV-2 est à l’origine de pneumonie potentiellement mortelle, les manifestations cliniques pouvant aller jusqu’au SDRA. Ce qui a été rapporté plus particulièrement chez les malades avec comorbidités cardiovasculaires. Méthodes Il s’agit d’une étude prospective de cas confirmés de COVID-19 hospitalisés pendant la période avril 2020 et août 2021. Les données anamnestiques, cliniques et paracliniques ont été relevées, analysés et comparées entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our results concerning plant families used by patients are very close to those recorded by other studies carried out in Algeria (Belmouhoub & Aberkane 2021, Brahimi et al 2022, Djouamaa et al 2022 and Morocco (Benkhaira et al 2021, Chaachouay et al 2021, Chebaibi et al 2022Flouchi et al 2023). However, there are a few differences in the frequency of plant species used compared to studies performed by other scientists (Brahimi et al 2022, Chebaibi et al 2022, Djouamaa et al 2022Flouchi et al 2023).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results concerning plant families used by patients are very close to those recorded by other studies carried out in Algeria (Belmouhoub & Aberkane 2021, Brahimi et al 2022, Djouamaa et al 2022 and Morocco (Benkhaira et al 2021, Chaachouay et al 2021, Chebaibi et al 2022Flouchi et al 2023). However, there are a few differences in the frequency of plant species used compared to studies performed by other scientists (Brahimi et al 2022, Chebaibi et al 2022, Djouamaa et al 2022Flouchi et al 2023).…”
Section: Discussionsupporting
confidence: 91%
“…In the last decade, many studies have reported the good biological effects of certain plants mentioned in this investigation, namely the antiviral, anti-inflammatory, immunostimulant, and antioxidant effects (San Chang et al 2013, Zhang et al 2014, Lim et al 2015, Li et al 2017, Çifci et al 2018, El-Saber Batiha et al 2020. Recently, other scientific studies have reported that these plants can really exert a potent antiviral effect against SARS-CoV-2 (Brahimi et al 2022, Chebaibi et al 2022, Djouamaa et al 2022Flouchi et al 2023).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations